Macronutrient status and indicators of acid-alkaline blood balance in cats with chronic renal failure - V. I. Holovakha; E. V. Mostovyi; A. O. Sliusarenko; O. V. Piddubnyak; N. I. Suslova; M. S. Matsinovich (Regulatory Mechanisms in Biosystems, 2020)
Chronic renal failure is a common pathology among cats. According to various literary sources, this pathology is found in 0.5–14.0% of cats. Pathology in cats in our studies is a consequence of glomerulonephritis. The diagnosis of chronic renal failure established on the basis of clinical, instrumental, and laboratory methods of blood and urine testing. Studies have found that chronic renal failure in cats is clinically characterized by apathy, anorexia, dry skin, odor of urea, vomiting, thirst, occurrence in the mouth of uremic ulcers (9.5% of patients), tachycardia (up to 177 beats per minute) tachypnoea (up to 45 respiratory movements per minute), hypertension. In the urine – hypostenuria, erythrocyturia, leukocyturia, kidney epithelium, hyaline and granular cylinders. According to echosonography – increase in echogenicity of the parenchyma, brain substance echone negative, cortico-brain differentiation erased. In the blood test – normochromic macrocytic anemia, thrombocytopenia, hyperazotemia (up to 27.9 mmol/L), hypercreatininemia (324 μmol/L), hyperuricemia (615 μmol/L), 4.6-fold increase in SDMA (symmetric dimethylargin). In chronic renal failure, cats have a significant change in the elemental composition of the blood. In particular, the Na+ content was increased by 3%, Ca2+ 1.6 times, P 2.1 times. Instead, the K+ level was reduced 1.9 times. Changes in acid-base equilibrium (ABE) were also detected: the pH decreased to 7.22; HCO3– by 34%, total CO2 by 32.3%, while anionic difference (AG) and buffer bases (BE) increased by 1.8 and 3.5 times, respectively. Such changes are characteristic of the development of lactic acidosis. The obtained experimental data on changes in mineral metabolism and acid-base equilibrium in the serum of cats in chronic renal failure supplement and clarify information on the pathogenic pathology of the kidneys in cats aged 5–10 years. Blood biochemical data can be used to improve early-stage diagnostics without clinical manifestations of chronic renal failure, their prevention and treatment, and to solve applied scientific problems in the field of nephrology and urology of small animals.